Physical and mechanical aging of wood-plastic composites. Non-destructive methods for quality control - Bobadilla Maldonado, Ignacio; Martínez, Roberto; Matini Behzad, Hamed; Hillig, Everton (Maderas. Ciencia y Tecnología, 2025)
This study investigates the relationship between laboratory aging, physical and mechanical changes, and the outcomes of non-destructive testing. A total of 45 composite specimens containing 60 % wood fiber, 35 % low-density polyethylene, and 5 % additives were tested. A laboratory aging process, consisting of water immersion at 20 ºC and 50 ºC for a total of 56 days, was applied to the specimens. During the aging process, several batches of specimens were extracted and tested to measure their physical (density) and mechanical properties (bending strength and modulus of elasticity). Non-destructive testing, including ultrasound and stress wave devices, a screw withdrawal resistance meter, and a penetration tester, were employed. Results indicated that temperature had a greater influence on the WPC deterioration than humidity. A decrease in density (2 % - 4 %) and a significant reduction in mechanical properties (20 % - 60 %) were observed. The non-destructive methods used proved to be reliable estimators of composite properties, especially ultrasound wave propagation, confirming previous findings on other materials.